TIR domain proteins: regulatory mechanisms in the tumor immune microenvironment, clinical translation strategies, and prospects for precision therapy applications - Lou, Jiatian; Gong, Chenlei; Gao, Xiaotao; Zhou, Jiaren; Wu, Qiyuan; Zheng, Xiaoliang; Cheng, Liyan (Frontiers in Immunology, 2025)
Toll/IL-1R (TIR) domain proteins, as central signaling hubs in innate immunity, dynamically orchestrate inflammatory responses and immune processes within the tumor microenvironment (TME) by mediating both MyD88-dependent and TRIF-dependent pathways. This review systematically elaborates on the dual regulatory roles of the TIR superfamily-encompassing toll-like receptors (TLRs), IL-1 receptors (IL-1Rs), and adaptor proteins-in tumor immunity, including the facilitation of stemness maintenance in cancer stem cells (CSCs) and the inductive mechanisms driving the formation of an immunosuppressive TME. From the perspective of clinical translation, the combinatorial therapeutic strategy of TIR agonists/inhibitors with immune checkpoint inhibitors (ICIs) represents a novel paradigm: the synergistic effects among TIR agonists/inhibitors, advanced nanodelivery systems, and radiotherapy-responsive prodrug technology provide a potential approach to address challenges such as systemic toxicity and low targeted delivery efficiency. Looking forward, the continuous advancement and broader application of TIR protein targets in the field of precision cancer immunotherapy hold great promise for offering new hope in the fight against malignant tumors.